Collaborative Skills of Pre-service Mathematics Teachers in Blended Learning - Lu'luilmaknun, Ulfa; Al Kautsar, Karin Selma; Apsari, Ratih Ayu; Triutami, Tabita Wahyu; Wulandari, Nourma Pramestie (Universitas Muhammadiyah Mataram, 2021)
Blended learning is a learning that combines face-to-face and online learning. Several studies have shown that blended learning has a positive effect on collaborative skills. The aim of this study is to determine the collaborative skills of pre-service mathematics teachers after using blended learning. The focus of this study is 4 indicators of collaborative work skills, namely quality of work, problem solving skills, working with others, and focus on the task. This type of study is a case study. The participants were 23 pre-service mathematics teachers in second year. Data collection was carried out using a collaborative questionnaire. Data were analysed using quantitative descriptive methods. The results showed that the criterion for quality work of students was 47.83% average. The criterion for problem solving skills was 47.83% very high. The criterion of working with others was 86.96% very high. The criterion for focus on the task was 82.61% very high. Therefore, blended learning possesses positive effects towards pre-service mathematics teachers.